2016
DOI: 10.1155/2016/9172157
|View full text |Cite
|
Sign up to set email alerts
|

Oral Administration of N-Acetyl-seryl-aspartyl-lysyl-proline Ameliorates Kidney Disease in Both Type 1 and Type 2 Diabetic Mice via a Therapeutic Regimen

Abstract: Kidney fibrosis is the final common pathway of progressive kidney diseases including diabetic nephropathy. Here, we report that the endogenous antifibrotic peptide N-acetyl-seryl-aspartyl-lysyl-proline (AcSDKP), the substrate of angiotensin-converting enzyme (ACE), is an orally available peptide drug used to cure kidney fibrosis in diabetic mice. We utilized two mouse models of diabetic nephropathy, streptozotocin- (STZ-) induced type 1 diabetic CD-1 mice and type 2 diabetic nephropathy model db/db mice. Inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 40 publications
1
31
0
Order By: Relevance
“…Authors confirm that all the experiments are performed in accordance to Japanese guidelines and regulations for scientific and ethical experimentation. The induction of diabetes in the CD-1 and C57Bl6 KsJ mice was performed according to the previously established experimental protocol 32 34 , 58 , 59 . In brief, 8-week-old CD-1 and C57Bl6KsJ mice were induced diabetes with the single intraperitoneal injection of streptozotocin (STZ) at 200 mg/kg in 10 mmol/l citrate buffer (pH 4.5).…”
Section: Methodsmentioning
confidence: 99%
“…Authors confirm that all the experiments are performed in accordance to Japanese guidelines and regulations for scientific and ethical experimentation. The induction of diabetes in the CD-1 and C57Bl6 KsJ mice was performed according to the previously established experimental protocol 32 34 , 58 , 59 . In brief, 8-week-old CD-1 and C57Bl6KsJ mice were induced diabetes with the single intraperitoneal injection of streptozotocin (STZ) at 200 mg/kg in 10 mmol/l citrate buffer (pH 4.5).…”
Section: Methodsmentioning
confidence: 99%
“…ACEi treatment increases the plasma level of AcSDKP by fivefold [16]. Earlier researches in support of antifibrotic activity of AcSDKP includes the inhibition of TGF-β-induced expression of plasminogen activator inhibitor-1 and α2 collagen in human mesangial cells by inhibiting the smad 2/3 signaling pathway [17]; Shibuya et al reported that AcSDKP prevented renal insufficiency and mesangial matrix expansion in diabetic db/db mice [18]; AcSDKP showed protective effects in various experimental animal models [19,20]. We here aimed to explore the ACEi and ARB actions on elevated DPP-4 level in regulating kidney fibrosis and to unravel the intermediary mechanisms involved.…”
Section: Introductionmentioning
confidence: 99%
“…23,25 Several studies have demonstrated that chronic administration of AcSDKP prevents kidney fibrosis and improves renal insufficiency in rodent models of diabetes. [26][27][28][29] Indeed, a recent study shows that mice lacking thymosin b4 have lower levels of renal AcSDKP and show an exacerbated kidney injury in response to angiotensin II infusion. 30 However, whether this tetrapeptide has a role in the abnormal sodium handling observed during diabetic nephropathy is unknown.…”
mentioning
confidence: 99%